Qlassic audit and inspection: single storey house project at Seri Iskandar, Perak / Muhammad Zulhusni Dahlan - Dahlan, Muhammad Zulhusni (Universiti Teknologi MARA UiTM,Perak, 2022)
Hua Yang Berhad has come a long way from its first eight four-storey shops at Jalan Gopeng, Ipoh. Today, the Group consistently delivers quality, affordable, integrated townships, high-rise residential projects and commercial lots across the nation.With over 21,229 properties worth RM5.145 billion completed across the nation, the company has honed and refined its skills in identifying areas within established and thriving districts to successfully introduce its concept of affordable lifestyle accommodation. Hua Yang currently has developments in Klang Valley, Johor, Perak, Negeri Sembilan, and Penang and is recognised as one of the nation’s leading property developers in the affordable home segment. This is a testament to their dedicated workforce and the close rapport Hua Yang has built with its customers.